Evaluation of tolerance to phosphorus shortage in cowpea (Vigna unguiculata L. Walp) in Cuba.. I. nutritive solution culture. - Gómez, Luis A.; Vadez, Vincent; Hernández, Germán; Sánchez, Támara; Toscano, Vidalina (Agronomía Mesoamericana, 2006)
Phosphorus deficiency is a major limiting factor for symbiotic nitrogen fixation and grain yield of legume crops in the tropics. Eight cowpea genotypes of wide use in Cuba, were grown in hydroponics solutions; supplying from 50 to 500 µM of P/plant/week. Nitrogen nutrition was dependent upon symbiotic N2-fixation on adding of 4 mmoles NO3/plant/week. Shoot growth was severely limited by P deficiency, while dry weight of roots increased in both groups of plants. Nodule formation was severely decreased by P deficiency, while specific nodule activity was increased in the atmospheric N2 fixing plants. Growth response of N2 plants was higher than that of NO3- fed plants due to P use efficiency, and revealed a the great large N2-fixation potential of the specie.